Side-to-side penoscrotal anastomosis: a reliable technique for repair of recurrent urethrocutaneous fistula in male children - Okoro, Philemon E.; Onyeanunam, Ngozi O. (International Surgery Journal, 2021)
Background: Surgical repair of urethrocutaneous fistulae (UCF) is relatively simple and results are often satisfactory. However, in some cases of UCF, recurrence results despite several attempts at repair. Reports are scanty on the management of such recalcitrant UCF. The aim of the study was to present our experience with recurrent UCF, and describes our technique of side-to-side penoscrotal anastomosis for repair of such fistulae. Methods: This was a 10 years analytical comparative study of the outcome of repair of recurrent UCF in paediatric patients using the simple double layer repair technique, and our technique of anastomosing the penis to the scrotum between 2008 and 2019 in our centre. Data obtained and analysed with SPSS 21 version included the number of previous attempts at repair, number, site and size of UCF, technique of repair, and the incidence of recurrence of UCF. Results: Nineteen patients were studied. Nine had conventional double layer repair of UCF with recurrence in 5 (55.6%). Two of the recurrent cases were added to the remaining 10 patients to make a total of 12 cases who had the staged repair by penoscrotal anastomosis (PSA) and there was no recurrence during the average follow up period of 1 year. P value was <0.05. Conclusions: Findings in this study suggest a superior outcome when the penoscrotal anastomosis is used for repair of recurrent UCF. We think it is better to apply this technique in cases of UCF which the surgeon considers potentially difficult than to wait to have a failed attempt before deploying it.